Challenges in the use of corticosteroids in the management of autoimmune hepatitis. (1st December 2019) - Chapman, Roger W; Aspinall, Richard J; Trivedi, Palak; Wright, Gavin; Heneghan, Michael
Abstract : Autoimmune hepatitis is widely assumed by health-care professionals to be a disease that is easily controlled through the use of corticosteroids and immunosuppressants but recent studies in the UK indicate highly variable treatment regimens and often unsatisfactory treatment outcomes, such as dependence on long-term high-dose steroids and ongoing need for liver transplantation in some cases. The therapeutic use of the systemically acting corticosteroid prednisolone results in unacceptable side effects in many patients. Recent evidence suggests that it is not always necessary to use high-dose steroids (>0.5 mg/kg/d) to attain remission; and side effects may also be minimised through more targeted therapy with the less systemically-absorbed corticosteroid, budesonide. The authors offer advice on the stratification of treatment for these patients and suggest changes to improve the services available for people with autoimmune hepatitis in the UK.